Reconciliation of Machine-Human Relations Through Ikigai Robotics: A Review - Bin Ramlan, Muhammad Nadzif (Mezurashii: Journal of Japanese Studies, 2024)
New dynamics in interactions between humans and machines have been generated as a result of the rapid advancement of artificial intelligence (AI) and robotics, which has significantly impacted human existence. In order to improve the interaction between humans and robots, this paper investigates the incorporation of the Japanese concept of Ikigai, or "reason for being," into the development and design of robotics. Ikigai is a concept that is predicated on four fundamental components: financial compensation, societal necessity, passion, and proficiency. Ikigai's correlation with increased lifespan and overall happiness suggests that it might be effectively used in the realm of technology. The research study underscores that integrating Ikigai ideas into robots may improve user acceptability and efficacy, especially among older persons. Collaborative design processes involving Ikigai experts lead to more user-friendly and meaningful interactions, highlighting the importance of user feedback. Ethical considerations are crucial when integrating Ikigai into AI development, as non-Western ethical frameworks promote fairness, reduce bias, and ensure AI systems align with human values. Personalisation of human-machine interactions through multimodal, interactive, and multitask machine learning supports this integration. User-centered research, collaborative design, iterative testing are among strategies for reconciliation that prioritise empathy, inclusivity, and ethical considerations. Co-designing with senior adults guarantees that technology is responsive to their requirements and contributes to their sense of purpose. This review concludes that integrating Ikigai principles into robotics can foster meaningful and beneficial interactions between humans and machines, promoting overall well-being. Future research should continue exploring Ikigai in various technological contexts to guide AI and robotics development toward human flourishing.